Time-phased geospatial siting analysis for renewable hydrogen production facilities under a billion-kilogram-scale build-out using California as an example. (1st August 2022) - Reed, Jeffrey; Dailey, Emily; Fong, Amber; Samuelsen, G. Scott
Abstract: For renewable hydrogen to be a significant part of the future decarbonized energy and transportation sectors, a rapid and massive build-out of hydrogen production facilities will be needed. This paper describes a geospatial modeling approach to identifying the optimal locations for renewable hydrogen fuel production throughout the state of California, based on least-cost generation and transport. This is accomplished by (1) estimating and projecting California renewable hydrogen demand scenarios through the year 2050, (2) identifying feedstock locations, (3) excluding areas not suitable for development, and (4) selecting optimal site locations using commercial geospatial modeling software. The findings indicate that there is a need for hundreds of new renewable hydrogen production facilities in the decades preceding the year 2050. In selecting sites for development, feedstock availability by technology type is the driving factor. Highlights: Extensive build-out of new renewable hydrogen facilities is needed for hydrogen economy. Zoning and terrain limit the potential renewable hydrogen production facility sites. Proximity to feedstock dominates cost-optimal site selection.